Mesenteric Lymphatic Targeting of Antiretroviral agents for Improved Treatment of HIV/AIDS - Chu, YenJu (2023)
Human immunodeficiency virus (HIV) is a worldwide pandemic that causes irreversible and unstoppable disease progression. Antiretroviral therapy (ART) can efficiently suppress viral replication and control the pace of HIV infection. However, discontinuing ART usually leads to rebound viremia and drug resistance when resuming ART. This is primarily due to establishment of latent HIV reservoirs in cellular and anatomical sites. Suboptimal levels of ART in viral reservoirs might allow the persistence of latent infection. Gut-associated lymphoid tissue (GALT), in particular mesenteric lymph nodes (MLNs), is the largest immune system in the body and an important HIV reservoir. This study selects two antiretroviral agents (ARVs), tipranavir (TPV) and dolutegravir (DTG), as candidate drugs for targeted delivery to the mesenteric lymphatic system. In view of the different physicochemical properties between TPV and DTG, this study was conducted by two different approaches: (1) Targeting of lipophilic drug TPV to mesenteric lymphatics by means of intestinal lymphatic transport using a long-chain triglyceride (LCT)-based formulation approach; (2) Developing a lipophilic ester prodrug system of hydrophilic drug DTG, combined with LCT-based formulation to target DTG to mesenteric lymph and MLNs.